ICT, Civil Registration and Branchless Banking: Sustaining the Social Cash Transfer (Aadim Journal of Multidisciplinary Research, 2025)
Information and Communication Technology (ICT) is a driving force of transformation process towards knowledge-based information society, that impact on political, economic and social development. The Government of Nepal (GoN) has started social cash transfer programme to its target groups like senior citizens, widow, children, etc since 1995 A.D. The programme is very popular especially with senior citizens and children. The list of beneficiary is maintained at local level in register and physical cash is distributed on quarterly basis through manual basis. The trend of data shows that every year number of beneficiaries is increased which indicates sustainability of social cash transfer. Civil registration is a process of recording natural events like birth, marriage, death, divorce and migration. The civil registration report shows that number of death records of children and senior citizens is high as compared to others. The primary objective of this research paper is to explore linkage of civil registration with social cash transfer programme and design architecture for sustainability of social cash transfer through branchless banking in Nepal. The researcher has applied quantitative methods, adopted survey method to collect primary data, found that current practice of maintaining data of social cash transfer and civil registration is manual and both programmes data are maintained independently. The researcher concluded that there is a direct linkage between civil registration and social cash transfer and designed architecture for social cash transfer through branchless banking.